2006
DOI: 10.1002/ppul.20455
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide in the management of childhood asthma: A prospective 6‐months study

Abstract: Fractional exhaled nitric oxide (FeNO) is elevated in asthma and reflects eosinophilic airway inflammation. The aim of this prospective, randomized, single-blind study was to examine whether the inclusion of repeated FeNO measurements into asthma monitoring leads to an improvement in asthma outcome. Forty-seven children with mild to moderate asthma were allocated to a FeNO group (n = 22) and to a control group (n = 25). In the FeNO group therapy was based on symptoms, beta-agonist use, lung function, and FeNO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
166
2
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(177 citation statements)
references
References 26 publications
4
166
2
5
Order By: Relevance
“…Duration of asthma was not ascertained. Baseline analysis of children's exhaled nitric oxide (eNO), a well accepted biological marker of airway inflammation (American Thoracic Society, 1999;Battaglia et al, 2005;Fritsch et al, 2006;Taylor, Pijnenburg, Smith, & Jongste, 2006;Gelb, Flynn Taylor, Shinar, Gutierrez, & Zamel, 2006;Zietkowski, Bodzenta-Lukaszyk, Tomasiak, Skiepko, & Szmitkowski, 2006), confirmed appropriate group placement of children within the asthma vs. no asthma group. (See 'Sample' description for actual data.)…”
Section: Asthma Diagnosismentioning
confidence: 99%
“…Duration of asthma was not ascertained. Baseline analysis of children's exhaled nitric oxide (eNO), a well accepted biological marker of airway inflammation (American Thoracic Society, 1999;Battaglia et al, 2005;Fritsch et al, 2006;Taylor, Pijnenburg, Smith, & Jongste, 2006;Gelb, Flynn Taylor, Shinar, Gutierrez, & Zamel, 2006;Zietkowski, Bodzenta-Lukaszyk, Tomasiak, Skiepko, & Szmitkowski, 2006), confirmed appropriate group placement of children within the asthma vs. no asthma group. (See 'Sample' description for actual data.)…”
Section: Asthma Diagnosismentioning
confidence: 99%
“…There may have been some bias in terms of outcome data completeness in the remaining four studies. Fritsch et al 103 did not report the reasons for participant withdrawal or correction for missing FeNO values and there may have been missing outcome data in the study by Petsky et al, 107 but this is unknown as only a conference abstract of this study was identified. In the study by Verini et al 105 it was reported that 64 patients were recruited; however, it was unclear whether this was the total number after dropout or whether no participants dropped out.…”
Section: Risk Of Attrition Biasmentioning
confidence: 99%
“…48 Another study in children presented 22.9 ppb as a FeNO cutoff with a sensitivity of 80% and a specificity of 60% for predicting exacerbation. 50 Emerging information indicates that assessment of within-individual changes in FeNO may be a more accurate method for In general for children, elevated eosinophil counts in sputum may be more sensitive for predicting asthma exacerbations or loss of asthma control after steroid reduction than elevated FeNO. 49 This is because high FeNO is not always pathological, whereas induced sputum eosinophil counts >1% is abnormal.…”
Section: ) Measuring Feno To Guide Asthma Management and Monitor Astmentioning
confidence: 99%